Child's Experience of Staying in Hospital from the Point of View of Parents and Medical Staff - Zlatka Cugmas; Anika Smeh (University of Maribor Press, 2018)
The study involved 84 parents of hospitalized children and 46 nurses or medical technicians. Hospitalization means distress for most children and activates the child's system of attachment to the parents. Parents and medical staff assessed the behaviour of children when admitted to hospital, while staying in hospital, and at dismissal from hospital. Answers to questions about the attitude of parents to their hospitalized child were obtained, whether hospital departments have a playroom and a nursery teacher, and who provides help to the child with difficulties adjusting to hospital. We found significant differences in the frequency of varieties of children's behaviour during the various stages of hospital stay. Of unsecure patterns of attachment resistance and disorganization were mainly expressed